Budaya Kerja Pada Ekosistem Tiga Perempat Coworking Space di Kota Semarang - Arina Khujjatul Khaq; Amirudin Amirudin; Riris Tiani (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
This study aims to explane the work culture of the three-quarters coworking space ecosystem at Semarang City The research subjects are creative workers and the internal team of the three-quarters coworking space. Data collection was carried out using participant observation methods, in-depth interviews with selected informants, and field observations. This research is a qualitative study using an ethnographic approach and the theory of cultural materialism proposed by Marvin Harris. The results found a pattern of activities of creative workers and the internal team of three-quarters of Coworking Space which is carried out every day as their habit and their views when doing work. Material and non-material cultures found in this study correlate with each other to form work culture in the three-quarter coworking space ecosystem. Work culture carried out by workers as a control of work intensity, as a way to achieve work goals, and psychological adaptation to workloads.